Discovery of Streptomyces marinisediminis sp. nov., a new thiolutin producing actinomycete isolated from Thai marine sediment - Rawirat Pansomsuay; Poowadon Fukasem; Pattama Pittayakhajonwut; Chakapong Intaraudom; Chanwit Suriyachadkun; Montri Yasawong; Ya‐Wen He; Somboon Tanasupawat; Qian Yang; Chitti Thawai (Scientific Reports, 2025)
exhibited strong antimicrobial activity against Gram-positive bacteria and led to the discovery of two promising secondary metabolites, thiolutin and 2,2-dioxidothiolutin, along with 8-amino-2H-benz[e][1,3]oxazine-2,4(3H)-dione, benadrostin, 2,3-dihydroxybenzamide, and 2-hydroxy-3-methoxybenzamide. In this study, 2,2-dioxidothiolutin was structurally confirmed for the first time by X-ray crystallographic analysis. Interestingly, thiolutin demonstrated strong anti-human small cell lung cancer (NCI-H187) activity, with an IC₅₀ value of 0.35 µg/mL, and also showed cytotoxicity against human breast cancer (MCF-7) cells, with an IC₅₀ value of 5.61 µg/mL.
Keywords: Genomics and Phylogenetic Studies; Microbial Natural Products and Biosynthesis; Marine Sponges and Natural Products